Evaluation of the bioremediation capability of sandfish, Holothuria scabra - Novilla, Schedar Rose M. (College of Fisheries, University of the Philippines Visayas, 2014)
An understanding of the bioremediation capability of Holothuria scabra is an important step in their aquaculture development and in acquiring basic information for designing efficient co-culture systems using this species. The sediment removal rate of H. Scabra, in terms of fecal production rate (FPR) and apparent digestibility coefficient (ADC), was determined in relation to its body size and organic matter (OM) content of the sediment. H. scabra (`10-150 g) were fed with shrimp feed containing different levels of OM (0, 0.46, 0.92, 1.38 and 1.84%). A positive correlation was detected between fecal production rate and body size of H. scabra (FPR = 0.07 (BW) + 1.80, r2 = 0.79, P<0.01, N = 17) ; while a negative correlation was observed between fecal production rate and OM (FPR = 2.921n (OM) = 2.99, r2 = 0.99, P<0.01, N =5) respectively. Furthermore, no correlation was observed between the apparent digestibility coefficient and body size of H. scabra (P>0.05), but a positive correlation was detected between the apparent digestibility coefficient and OM (ADC = 95.45(OM)0.05, r = 0.95, P<0.05, N =5). Results showed that the levels of OM of shrimp feed affected FPR and ADC, thus the co-culture of H. scabra and shrimp may be feasible in terms of energy budget and nutrient provision.